Influencia del taller de Juegos Recreativos “Nueva Vida” en el mejoramiento de la Inteligencia Emocional de los niños de 5 años de la Institución Educativa 1564 “Radiantes Capullitos” de la urb. Chimú-Trujillo 2015 - Alvarado Vargas, Rosa María (2017)
The present research originated from the experiences we got in our pre professional practices at I.E "Radiantes Capullitos”, this experience allowed us to observe that children are limited in the expression of their emotions. Therefore we take as an initiative to research how we could help them to improve their emotional intelligence, through a recreational games workshop called “Nueva Vida” that consists on different kinds of games that would help children to identify, express and deal with their emotions._x000D_ It is an applied and quasi-experimental research, with pre and post test group. Pre test results show that before the workshop "Nueva Vida", children had some disorders in their emotions and few of them had control over their emotions._x000D_ After applying the Recreational Games Workshop "Nueva Vida" to improve emotional intelligence, according to the post-test, children showed a significant improvement to deal with their emotions against different situations in their life.